IMPLIKASI PROSES TAKE-OVER BANK SWASTA NASIONAL GO PUBLIC TERHADAP TINGKAT KESEHATAN DAN KINERJA BANK - Mintarti, Sri (University of Merdeka Malang, 2009)
The purpose of this research was to know the implication process of take-over inNational Private Banks to the degree of banks health and performance. The samples were 5national private banks which had asset more than 20 trillion and the structure of foreignownership was above 51%. Independent variable used was ratio CAEL consisted of CAR, LDR,BOPO, and NPL while dependent variable used was ROA. By using multiple regression analysis,it was found that CAR, BOPO, LDR and NPL simultaneously had an influence to ROA, while onthe whole the result of banks health degree in 5 national private banks which did take overusing CAEL method showed relative good performance.